Advanced airship technologies and design approaches - Hunt, Philip V. (Library of flight., 2015)
This book outlines important airship design and practicability considerations and suggests a design approach that will result in successful development programs and lead to airships that are in synch with 21st century aviation practices and advanced military commercial operating utility needs. The need for economical heavy lift transportation as well as specialized intelligence, surveillance, and reconnaissance (ISR) platforms is an opportune time to look again at lighter-than-air vehicle technology. An airship revival has proven difficult due to failed or canceled airship programs proving corrosive to the perceived viability of the technology. If the present revival of interest in airships is to avoid a new generation of failures, or an inability to achieve promised results, it is essential to introduce an era of more prudent airship design, clear vision, and better management. --